Odpowiedzi

2009-04-02T16:00:43+02:00
A)
3x + 2 = 2x +5/ -2
3x = 2x +3/ -2x
1x = 3
----
9+2=6+5
11=11
b)
3x-15=x-3/ +15
3x=x+12/-x
2x=12/:2
x=6
---
18-15=6-3
3=3
c)
4(x+1)=6x
4x +4=6x/-4
4x=6x -4/-6x
-2x=-4:(-2)
x=2
---
8+4=12
12=12
d)
3(x+1)=2(2x-1)
3x+3=2x -2/-3
3x=2x-5/-2x
x=-5
---
-15+3=-10-2
-12=-12
e)
3(2x-1)-2(4x+3)=7-4(x+1)
6x-3-8x-6=7-4x-4
-2x-9=7-4x/+4x
2x-9=7/-9
2x=-7/:2
x=-3,5
---
3(-7-1)-2(-14+3)=7 -4(-3,5+1)
-21-3+28-6=7+24-4
------------------
Proszę bardzo :))
  • Użytkownik Zadane
2009-04-02T16:02:01+02:00
A) x=3
b) 2x=12
x=6
c)4x+4=6x
-2x=-4
x=2
d) 3x+3=4x-2
-x=-5
x=5
e) 6x-3-8x-6=7-4x-4
2x=-6
x=-3